2019
DOI: 10.1073/pnas.1905570116
|View full text |Cite
|
Sign up to set email alerts
|

Decreased humoral immunity to mumps in young adults immunized with MMR vaccine in childhood

Abstract: In the past decade, multiple mumps outbreaks have occurred in the United States, primarily in close-contact, high-density settings such as colleges, with a high attack rate among young adults, many of whom had the recommended 2 doses of mumps-measles-rubella (MMR) vaccine. Waning humoral immunity and the circulation of divergent wild-type mumps strains have been proposed as contributing factors to mumps resurgence. Blood samples from 71 healthy 18- to 23-year-old college students living in a non-outbreak area … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 58 publications
(105 reference statements)
0
31
0
Order By: Relevance
“…The results also indicated that some of the analyzed immunological parameters and percentage of seropositive subjects in the pre-teen cohorts (10-12 y) tended to be higher than in the young adults cohorts (16-20 y) for both vaccines, which confirmed that the older age of the women enrolled is a parameter that might affect immunogenicity [51][52][53][54]. We also observed high levels of anti-HPV-6 and HPV-11 humoral responses (IgG titers and memory B cells) in subjects who received the Gardasil vaccine approximately six years earlier, which implied a sustainable and strong immunologic response also against the low-risk HPV types elicited by the quadrivalent vaccine and confirming other observations [25].…”
Section: Discussionmentioning
confidence: 80%
“…The results also indicated that some of the analyzed immunological parameters and percentage of seropositive subjects in the pre-teen cohorts (10-12 y) tended to be higher than in the young adults cohorts (16-20 y) for both vaccines, which confirmed that the older age of the women enrolled is a parameter that might affect immunogenicity [51][52][53][54]. We also observed high levels of anti-HPV-6 and HPV-11 humoral responses (IgG titers and memory B cells) in subjects who received the Gardasil vaccine approximately six years earlier, which implied a sustainable and strong immunologic response also against the low-risk HPV types elicited by the quadrivalent vaccine and confirming other observations [25].…”
Section: Discussionmentioning
confidence: 80%
“…Thirty of these sites were conserved between our sequences and a cell-passaged clinical strain that was isolated from Iowa in 2006 (accession: JX287385), near the beginning of mumps resurgence in the US. The Iowa 2006 strain was previously shown to be neutralized by sera from both vaccinated and naturally infected individuals, but to a lower degree than neutralization of the Jeryl Lynn strain itself [29][30][31], raising the possibility that some of these mutations may confer partly reduced neutralization susceptibility. In addition, we observed 2 positions at which our sequences differed from both the Jeryl Lynn and the Iowa 2006 strains.…”
Section: Resultsmentioning
confidence: 99%
“…This is significantly higher than is found for other common vaccine antigens such as mumps, measles, rubella, or varicella-zoster virus (VZV) ( Fig. 1B,C; Rasheed et al 2019;Eberhardt et al 2020). Additionally, influenza vaccine-specific plasma cells account for ∼1% of total IgG plasma cells in the bone marrow ( Fig.…”
Section: High Preexisting Immunity To Influenza In Humansmentioning
confidence: 80%
“…Influenza vaccine-reactive IgG, IgA, and IgM antibody titers were measured in healthy human adults by ELISA (n = 38) (A). Frequency of antigen-specific memory B cells specific for mumps, measles, rubella, and influenza (B), or of VZV and influenza (C) were measured by stimulation of PBMCs and quantification by ELISpot as previously described (Rasheed et al 2019;Eberhardt et al 2020). VZV and influenza-specific IgG bone marrow plasma cells were quantified by ELISpot and plotted as the percentage of total IgG secreting bone marrow plasma cells (D).…”
Section: Memory Recall Responses After Vaccinationmentioning
confidence: 99%